Genetic Characterization of mcr-1-Positive Multidrug-Resistant Salmonella enterica Serotype Typhimurium Isolated From Intestinal Infection in Children and Pork Offal in China - Zhang, Haoran; Xiang, Ying; Huang, Yong; Liang, Beibei; Xu, Xuebin; Xie, Jing; Du, Xinying; Yang, Chaojie; Liu, Hongbo; Liu, Hongbo; Wang, Hui; Yang, Mingjuan; et al. (Frontiers in Microbiology, 2022)
With the rapid emergence of plasmid mediated colistin resistance gene mcr-1, the increased resistance of Salmonella attracted extensive attention. Here we reported eleven multidrug-resistant Salmonella strains harboring mcr-1 in China. They all showed resistance to colistin, and additionally one of them was also resistant to ceftriaxone and azithromycin which was isolated from children stool sample. We screened 1454 strains of Salmonella for mcr-1 gene through PCR, and these strains are all preserved in our laboratory. Antimicrobial sensitivity analysis was carried out on the screened mcr-1 positive strains. Genetic polymorphism analysis of S. Typhimurium was performed by using the Pulsed-Field Gel Electrophoresis. The plasmids harboring mcr-1 were identified by S1-PFGE and southern blotting. Plasmid conjugation assays were carried out to analysis the transferability of colistin resistance. The plasmids harboring mcr-1 were characterized by sequencing and bioinformatic analysis. Eleven S. Typhimurium strains harboring mcr-1 with colistin resistance (MICs 4μg/ml) were identified, which were isolated from children and pig offal in China, and all of them were multidrug-resistant strains. PFGE revealed that some strains which isolated from different samples and areas have the same genotype. S1-PFGE and southern blotting showed that three plasmids of different sizes all carried the mcr-1 gene, the sizes are about 33kb, 60kb and 250kb, respectively. the plasmid conjugation assays revealed that Salmonella might have acquired mcr-1 harboring plasmids by horizontal transfer of plasmids. Sequencing and plasmid type analysis revealed these plasmids were IncX4, IncI2 and IncHI2 plasmid types. Among of them, IncX4 and IncI2 plasmids had extremely similar typical backbone, and contain one mcr-1 resistance gene. IncHI2 plasmid contained multiple-resistant genes including blaCTX-M, oqxB, sul, aph, aadA and blaTEM, which should be taken seriously.We identified and described the characteristics of eleven mcr-1 harboring S. Typhimurium strains in China. Our findings indicate that the mcr-1 gene can effectively spread among intestinal bacteria through horizontal transfer of three types of plasmids. Moreover, IncHI2 plasmid can also mediate the transfer of multiple other drug resistance genes. Therefore, it is imperative for constant surveillance of mcr-1 harboring S. Typhimurium to prevent colistin resistance spread.